Preservation of DNA integrity in biological material. Issue 1 (December 2019) - Burrows, Adria Michelle; Kasu, Mohaimin; D'Amato, Maria E.
Abstract: We have designed a buffer for preservation of DNA in biological material at room temperature. In this work we evaluated the integrity of DNA from saliva, stored for 4 years and blood stored for 4 months at room temperature. Parallel tests were conducted with other commercial systems. No sign of degradation was detected in the tested samples.